The Influence of Brand Image, Product Quality, and Electronic Word of Mouth on Purchase Decision on Cargloss Helmet Products (Study on Cargloss Helmet Product Users in Surabaya) - Erniz Regi Nobelyta Zuniyanto; Indah Respati Kusumasari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the significant influence of brand image, product quality, and electronic word of mouth both simultaneously and partially on purchase decisions on Cargloss helmet products in Surabaya. This type of research is associative research with a quantitative approach. Measurement of variables using a Likert scale with criteria strongly disagree to strongly agree. This sampling technique uses a non-probability sampling method by applying a purposive sampling approach. In this study, the population used was residents of Surabaya City with a sample of 100 respondents who were Cargloss helmet users. The data collection method uses a questionnaire distributed to respondents who match the criteria. Data analysis techniques using the SPSS version 26 programme. This study states that the variables Brand Image, Product Quality, and Electronic Word of Mouth simultaneously have a significant effect on Purchase Decision on Cargloss helmet products in Surabaya. The results also show that there is a significant effect of Brand Image, Product Quality, and Electronic Word of Mouth partially on Purchase Decision on Cargloss helmet products in Surabaya.